CHARACTERIZATION OF STREPTOMYCES sp. 45I-3 XYLANASE - Anja Meryandini; Deden Saprudin; Prima Agung Prihandono; Alina Akhdiya; Trio Hendarwin (BIOTROPIA, 2007)
Streptomyces sp 45I-3 producing xylanase was isolated from Kalimantan soil sample. Crude enzyme (produced by centrifuging the culture at 14000 rpm for about 5 minutes) and purified xylanase has an optimum condition at pH 5 and 50 oC.Â  Crude xylanase have half-life time of 2 hours 9 minute at 50 oC, whereas purified xylanase has half-life time of 12 hours. The molecular mass of purified xylanase was determined to be 43.2 and 39.2 kDa.